Problems that the students of tercer ciclo face in the large english class at Centro Escolar Rafael Álvarez Lalinde en Santa Ana city - Chávez Chávez, Norma Lizeth; Hernández Mendoza, Teresa de Jesús; Juárez Contreras, Gerardo Alberto; Garay Salinas, Ricardo (San Salvador, El Salvador : Universidad de El Salvador, 2012)
The main purpose of this research project was to understand how problems of discomfort, control, individual attention, evaluation, and learning effectiveness take place in the large English class with the students from 7th to 9th grade at Centro Escolar Rafael Alvarez Lalinde in Santa Ana city. Thus, the investigation was aimed at answering the question: How do problems of discomfort, control, individual attention, evaluation, and learning effectiveness take place in the large English class with students from 7th to 9th grade at Centro Escolar Rafael Alvarez Lalinde in Santa Ana city? This was a qualitative research study because it was used to gain insight into people's attitudes, behaviors, concerns, meanings, and culture. Besides, it includes a description of the main problems found in the large English class. The Ethnography and Photography methods were used in this research because ethnography is focused on describing a culture or way of life in the participants’ points of view and photography enriches it by taking into account recording equipment. The unit under study was 18 out of 84 students from 7th to 9th grade at Centro Escolar Rafael Alvarez Lalinde in Santa Ana city. Subsequently, it was found out that the problems of discomfort, control, individual attention, and evaluation affect in great manner students and teachers in large classes since they are obstacles for learning effectiveness. Even though the students’ lack of interest seemed to be a main factor here, the other problems mentioned above only contribute to make the situation worst. Therefore, some recommendations are included to be taken into account in order to minimize the effect of the problems.
Anexos.
Tesis -- (Licenciatura en Idioma Inglés, opción Enseñanza) -- Universidad de El Salvador, San Salvador, 2012
Bibliografís: hoja 45
Audiencia general
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza; Educación primaria